الرشاقة التنظيمية وتأثيرها التفاعلي في العلاقة بين القيادة الريادية والتفوق التنظيمي - عبدالله, ده رون فريدون; محمود, عثمان كريم; محمد, برشنك صالح; عبدالله, دنيا احمد; صادق, زانا مجيد (Sulaimani Journal for Humanities, 2021)
The current study aims to determine and analyze the interactive effect of organizational agility on the relationship between entrepreneurial leadership and organizational excellence at Korek Telecom Company in Erbil city. The analytical descriptive method was adopted to describe the theoretical framework for the concepts and variables of the study, and then analyze the correlation relationship and effect between the dependent and independent variable on the one hand, and the interactive variable and its effect on the assumed relationship between the other two variables on the one hand. The researchers used the questionnaire survey as a tool to collect primary data from the study sample taken from the study population represented the workers in the field of study, which is Korek Telecom Company in Erbil. The SPSS program Version 25 was adopted to analyze the required statistical analyzes such as the Cronbach alpha coefficient in addition to find the values of mean and standard deviations for the dimensions of the study variables along with testing the study hypotheses using the Pearson correlation coefficient and the Multiple Regression analysis. This study found that there is a statistically significant correlation and regression relationship between the study variables and their dimensions in the researched companies from the perspective of their employees on the one hand, and this relationship is effected by the action of the interactive variable influenced by statistical significance on the other side according to the results of statistical analyzes which is useful to prove study hypotheses. The study presented a set of recommendations, including that the researched company adopts organizational agility more due to its interactive effect in strengthening the existing relationship between entrepreneurial leadership and organizational excellence.
Keywords: Organizational Agility; Entrepreneurial Leadership; Organizational Excellence; Korek telecom for communication; Erbil city